PENGAWASAN KUALITAS AIR BERSIH OLEH DINAS KESEHATAN KOTA PEKANBARU (STUDI KASUS DI KECAMATAN RUMBAI PESISIR TAHUN 2013) - Mhd Sony Septyan; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Clean water is a source of survival for the whole society on the face of the earth. Therefore, monitoring of water contained in the Act of 1945, Article 33, paragraph 3 states that: "The earth, water and natural resources contained therein controlled by the State and shall be used for public welfare. Regional Regulation No. 5 of 2005 Article 7 paragraph 1 describes the "Supervision and inspection of water quality in use must be checked quality. Pekanbaru City Health Department is responsible for overseeing the full water standards in the city of Pekanbaru is managed by PDAM Tirta Siak Pekanbaru in its function is not maximal in Pekanbaru. Departing from the above phenomenon researchers interested in examining the Dept. of Health and taps Pekanbaru City sebagain institutions in carrying out its functions relating to the title "Water Quality Monitoring in Pekanbaru City Health Office (case study in the District Coastal Rumbai 2013)The fundamental problem in the actual monitoring process conducted by the City Health Department Pekanbaru where maximal surveillance conducted, should the Department of Health set up, develop and oversee the implementation of the use of water in order to maintain and improve public health and also improve service to the public and to prevent the use of water endanger public health from water quality does not meet the health requirements.But the phenomenon that occurs Monitoring is not running as it should, due to the fact that water quality in the District Coastal Rumbai not meet standards due to a lack of oversight conducted by the Health Department to take full responsibility in supervision. The theory which I use as a tool of analysis in this study is the theory of Supervision. While the methods used in this study is qualitative, ie trying to analyze the efforts and the factors and explain the data obtained from the observations and aim to reinforce and strengthen a theory so as to obtain information about the current situation. Data collection techniques in this study is to use interview techniques and documentation.It can be concluded, this lack of oversight of research conducted by the Department of Health on the quality of water distributed by Tirta Siak, hence the need for further scrutiny to follow the constraints that occur and realize the clean water standards to meet the needs of the community.Keywords: Control, Department of Health, Water Quality